Effects of chronic stress exposure on the anxiogenic behavior and regenerative capacity of zebrafish (Danio rerio) (2021)
Environmental stimuli such as daily routine, dietary habits and stress are strongly related to the physiology of our body. However, we still do not know entirely how this relationship occurs. The zebrafish has been used as a promising model in behavior, stress, anxiety and neuroscience research, thanks to its homology with vertebrates like rodents and mammals. Here in this study, we report preliminary results about the effect of chronic stress on the regeneration of the caudal fin in zebrafish (Danio rerio). We exposed fish to a UCS protocol to stimulated chronic stress conditions and performed behavioral tests (open field and light/dark preference) to evaluated anxiety-like behavior. Then we cut the lower part of the caudal fin to evaluated the effect of the stress on tissue regeneration.